2014
DOI: 10.4315/0362-028x.jfp-13-515
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Behavior of Multidrug-Resistant and Pansusceptible Salmonella during the Production and Aging of a Gouda Cheese Manufactured from Raw Milk

Abstract: Outbreaks of salmonellosis have been linked to the consumption of cheese, and emerging multidrug-resistant (MDR) strains of Salmonella may be more virulent and more tolerant than less resistant strains to stresses encountered in food production, which may enhance the survival of these resistant strains in cheese. This study was conducted to compare the behavior of MDR and pansusceptible Salmonella strains during the manufacture and aging of Gouda cheese and compare pathogen recovery via several rapid and tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Unsafe water sources in the Nile Delta regions, unsanitary conditions in food production environments, poor personal hygiene, and the health status of food handlers increase the risk of cross-contamination of retail food with virulent and AMR enteropathogenic bacteria, which could be a potential vehicle for foodborne diarrheal illnesses [12,19,20]. To date, limited studies have addressed the occurrence of virulence and β-lactams resistance genes in Salmonella strains isolated from Rumi and pasteurized Kariesh cheeses across rural areas in Lower Egypt, particularly in the Nile Delta region.…”
Section: Discussionmentioning
confidence: 99%
“…Unsafe water sources in the Nile Delta regions, unsanitary conditions in food production environments, poor personal hygiene, and the health status of food handlers increase the risk of cross-contamination of retail food with virulent and AMR enteropathogenic bacteria, which could be a potential vehicle for foodborne diarrheal illnesses [12,19,20]. To date, limited studies have addressed the occurrence of virulence and β-lactams resistance genes in Salmonella strains isolated from Rumi and pasteurized Kariesh cheeses across rural areas in Lower Egypt, particularly in the Nile Delta region.…”
Section: Discussionmentioning
confidence: 99%
“…66 The cited authors emphasize the need to use improved hygienic conditions to reduce the prevalence of resistant bacteria in dairy products.…”
Section: Bacteria In the Food Chainmentioning
confidence: 99%
“…Although the incidence of resistant bacteria has been found to be higher in retail meat (69.8%) than in dairy (62.5%) products, many studies that have included dairy products have reported the presence of resistant organisms in retail cheeses, salads, ham, and raw meat, in cow’s milk and dairy products, in goat’s and sheep’s milk, and in Gouda cheese manufactured from raw milk . The cited authors emphasize the need to use improved hygienic conditions to reduce the prevalence of resistant bacteria in dairy products.…”
Section: Occurrence Of Antibiotic-resistant Bacteria In the Food Chainmentioning
confidence: 99%
See 1 more Smart Citation